Synthesis and biological evaluation of 2,4,5-trisubstituted thiazoles as antituberculosis agents effective against drug-resistant tuberculosis - Karale, Uttam B.; Krishna, Vagolu Siva; Krishna, E. Vamshi; Choudhari, Amit S.; Shukla, Manjulika; Gaikwad, Vikas R.; Mahizhaveni, B.; Chopra, Sidharth; Misra, Sunil; Sarkar, Dhiman; Sriram, Dharmarajan; Dusthackeer, V. N. Azger; et al. (European Journal of Medicinal Chemistry, 2019)
The dormant and resistant form of Mycobacterium tuberculosis presents a challenge in developing new anti-tubercular drugs. Herein, we report the synthesis and evaluation of trisubstituted thiazoles as antituberculosis agents. The SAR study has identified a requirement of hydrophobic substituent at C2, ester functionality at C4, and various groups with hydrogen bond acceptor character at C5 of thiazole scaffold. This has led to the identification of 13h and 13p as lead compounds. These compounds inhibited the dormant Mycobacterium tuberculosis H37Ra strain and M. tuberculosis H37Rv selectively. Importantly, 13h and 13p were non-toxic to CHO cells. The 13p showed activity against multidrug-resistant tuberculosis isolates. (C) 2019 Elsevier Masson SAS. All rights reserved.

Catalyst-free regioselective [3+2] cycloadditions of alpha,beta-unsaturated N-arylnitrones with alkenes to access functionalized isoxazolidines: a DFT study - Ghosh, Arnab; Mane, Manoj V.; Rode, Haridas B.; Patil, Siddappa A.; Sridhar, Balasubramanian; Dateer, Ramesh B. (Chemistry-An Asian Journal, 2020)
The catalyst-free regioselective [3+2]-cycloaddition of alpha,beta-unsaturated N-arylnitrones with alkenes are developed. The series of synthetically important functionalized isoxazolidines are prepared in good to excellent yields by step economic pathway under ligand and transition-metal-free conditions. The regioselective cycloaddition pathway supported by control experiment and computational study.
Keywords: DFT study; isoxazolidines; metal and ligand free; nitrone cycloaddition; Regioselective